1972
DOI: 10.1139/f72-141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eutrophication on Salmonid Communities in Oligotrophic Lakes

Abstract: 972. Effects of eutrophication on salmonid communities in oligotrophic lakes. J' Fish' Res. Bd. Canada 29:975-983.Oligotrophic lakes respond to progressive eutrophication by a sequence of predictable events. Increased nutrient loads and subsequent increased plant production result in alterations in the abiotic environment, including changes in the color and transparency of the water, increased turbidity, oxygen depletion in the hypolimnion, and increased chemical stratification. The physico-chemical changes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 0 publications
6
57
0
3
Order By: Relevance
“…Anthropogenic eutrophication was a worldwide problem during the second half of the 20th century, and it affected many lakes dominated by coregonids (Christie 1972;Colby et al 1972;Grimås et al 1972). In many of these lakes, eutrophication has been successfully abated in the meantime, and the lakes have returned or are returning to preeutrophication levels ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic eutrophication was a worldwide problem during the second half of the 20th century, and it affected many lakes dominated by coregonids (Christie 1972;Colby et al 1972;Grimås et al 1972). In many of these lakes, eutrophication has been successfully abated in the meantime, and the lakes have returned or are returning to preeutrophication levels ).…”
Section: Discussionmentioning
confidence: 99%
“…The first theoretical ichthyocoenose models bound community shifts with trophic status, but they were developed for northern, initially oligotrophic, temperate lakes (Colby et al 1972, Prejs 1978) and thus were not appropriate for European reservoirs, as concluded by Kubečka (1993). Reservoirs can be eutrophicated from the moment of their origin, the biotic interactions are more complex and influenced by more dynamic hydrological regimes and management practices than in natural lakes (Hrbaček 1984, Straškraba 1998, Wagner et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fish species composition of lakes are generally affected by eutrophication, (e.g. COLBY et al, 1972), shore line degradation, migration barriers (RUHLÉ, 1996), and acidification Ecological Assessment of Lakes (SCHINDLER et al, 1989;RASK and TUUNAINEN, 1990). A significant ecological deficit in the species composition is the extinction of Arctic char in Irrsee as a result of the eutrophication and subsequent hypolimnic oxygen deficits during the 1970ies and 1980ies (JAGSCH, 1987).…”
Section: Species Compositionmentioning
confidence: 99%